Gambaran Pengetahuan Inter Professional Collaboration Pada Profesional Pemberi Asuhan Di Rumah Sakit Khusus Propinsi Jambi: Kajian - Ellis Mawarni; Dachriyanus Dachriyanus; Esthika Ariany Maisa; Jufri Al Fajri (Universitas Batanghari Jambi, 2019)
Interprofessional collaboration (IPC) between nurses and doctors is associated with good outcomes for patients, especially in hospitalizations. Different professional cultures can be a barrier to nurses and doctors in an IPC effective and efficient. Effective IPC is important to ensure patient safety. To analyze how the image of Professional Care Givers is different in implementing IPC at Jambi Special Hospital. The research was cross-sectional, the population were nurses, doctors, pharmacists and nutritionists in Jambi Province Special Hospital 105 samples. Sampling with total sampling. AITCS research instruments that have been modified as needed. Most of the application of IPC to Professional Care Givers in Jambi Province Special Hospital both on the partnership dimension, coordination, shared decision-making is only on the clearest reciprocal differences in the dimension of cooperation which is more than half less good. Conclusion: It is expected that the special hospital of Jambi Province will organize more integrated patient center care, which will have consequences for the implementation of the IPC, especially in terms of perceived cooperation.